Recycling Ablution Water (Wudu’) Using Membrane Water Treatment: A Study from Fiqh Halal Perspective - Wan Ainaa Mardhiah Wan Zahari; Irwan Mohd Subri; Azman Ab Rahman; Arwansyah Kirin; Faisal Husen Ismail (JURIS (Jurnal Ilmiah Syariah), 2022)
Water conservation is essential in Islam. The reuse of water for ablution through the process of water treatment is one way of water conservation. However, discussions and debates occurred because the source of water used for the treatment is categorized as musta’mal, which is pure but not purified and may contain mutanajjis water. This article proposes a model of treatment and purification of ablution water in mosques or surau using membrane water treatment for water reuse. This article uses a qualitative method focusing on document analysis regarding fiqh books, articles and guidelines related to water treatment technology. According to the fiqh and science, this study found that water treatment for treating used ablution water using membrane water filter is pure and clean.